2015
DOI: 10.1242/dev.120741
|View full text |Cite
|
Sign up to set email alerts
|

Multiple cell and population-level interactions with mouse embryonic stem cell heterogeneity

Abstract: Much of development and disease concerns the generation of gene expression differences between related cells sharing similar niches. However, most analyses of gene expression only assess population and time-averaged levels of steady-state transcription. The mechanisms driving differentiation are buried within snapshots of the average cell, lacking dynamic information and the diverse regulatory history experienced by individual cells. Here, we use a quantitative imaging platform with large time series data sets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 30 publications
3
40
0
Order By: Relevance
“…Since asymmetric divisions, in particular in size, are important for fate specification in a number of stem cell types (3,5,6,12), we asked if ES cells display asymmetries at cell division. We monitored cell divisions in ES cells stably expressing H2B-RFP to label DNA (21). We tested that the cell line could contribute to all the tissues by injecting it in a blastocyst, which gave rise to a viable mouse ( Figure S3A).…”
Section: Es Cells Present Strong Size Asymmetries Between Daughter Cementioning
confidence: 99%
“…Since asymmetric divisions, in particular in size, are important for fate specification in a number of stem cell types (3,5,6,12), we asked if ES cells display asymmetries at cell division. We monitored cell divisions in ES cells stably expressing H2B-RFP to label DNA (21). We tested that the cell line could contribute to all the tissues by injecting it in a blastocyst, which gave rise to a viable mouse ( Figure S3A).…”
Section: Es Cells Present Strong Size Asymmetries Between Daughter Cementioning
confidence: 99%
“…However, the long-standing dogma that ESCs have a shorter G1-phase than somatic cells was mainly based on studies performed in serum-cultured ESCs 9,26 . Recently, we and others have shown that 2i ESCs have a much longer G1-phase as compared to serum ESCs 7,27 . How these differences in cell cycle between serum and 2i ESCs affect the biological processes that take place during G1-phase has remained unclear.…”
Section: Discussionmentioning
confidence: 81%
“…An ESC culture bases on a dynamic equilibrium between cells that self-renew and others that differentiate mainly under the control of a small transcription factor network with three core components: Nanog, Oct4 and Sox228. This fragile equilibrium is highlighted by the stemness gene expression at single cell level: not all the cells co-expressed the pluripotency genes27444546, but this is in step with the fact that quiescence, proliferation and differentiation processes are dynamic events inside a SC population. It is important to underline that we used ESC to investigate the capacity of the extraembryonic environment to maintain the characteristics of foreign cells and not for therapeutic purposes; considering this aim, E13.5 was the suitable gestational age to perform IUT because the embryo at this stage has the dimension to allow the injection into the amniotic cavity without damaging the fetal structures.…”
Section: Discussionmentioning
confidence: 99%